The Rural Roads Impact on Education Performance in Antioquia (Colombia): an ordered probit model (2017)
This paper aims to determine the impact of the Antioquia department’s road system, particularly the rural roads system, on the probability of advancement in the educational achievement of students from rural areas in high schools in Antioquia, Colombia. For this we propose an ordered logistic model of educational performance, defining as a independent variable a transformation of the rural road densities in relation to the supply of sewage, energy, telephone service, among others, with the aim of capturing the variability and dispersion of rural areas in each municipality. The results show that rural roads influence the probability of increasing educational performance for rural students.